PERANAN PEMERINTAH KABUPATEN KARANGANYAR UNTUK PEMBERDAYAAN PASAR RAKYAT DI KABUPATEN KARANGANYAR - Risamtyo, Adi Bintang; Achmad, Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
ADI BINTANG RISAMT Y O. 2019. E0013012. T H E ROL E OF T H E GOVERNMENT OF THE KARANGANYAR DISTRICT FOR EMPOWERMENT OF THE PEOPLE’S MARKET IN KARANGANYAR DISTRICT. Faculty of Law, Sebelas Maret University, SurakartaThis legal writing is to examine the role of the Karanganyar district government in market empowerment that can compete in the current era. In addition, it also examines the obstacles faced by the Karanganyar Regency Government in implementing good market empowerment. The main objective of the role of the Karanganyar Regency Government is as a facilitator in the participatory market empowerment process.This legal research uses descriptive empirical juridical research, the source of legal material consists of primary legal material and secondary legal material. The legal material collection technique used is related literature studies from print and internet media and field techniques that use interview methods.Based on the research and discussion, it can be concluded that the role of the Karanganyar Regency Government in Empowerment Implementation that can compete in the current competition era in Karanganyar Regency is carried out as a facilitator of empowerment planning review in Karanganyar Regency and managing the budget that has been planned by the Karanganyar Regency Government. planning stage, implementation stage, monitoring and evaluation stage. The obstacles faced are First, lack of budget or funds. Second relocation of traders. Third, there are third parties who are not satisfied with the arrangement of the market. Fourth, the lack of competitiveness of the People’s Market is compared to the Modern Market. Fifth, the draft regional regulation has not yet been passed. Sixth lack of human resources who master and understand about the people’s market. The seventh is a bad stigma about the People’s Market.